Pengaruh tanggung jawab sosial terhadap niat beli dengan mediasi citra merek pada produk telkom - Mochammad Abdul Muid Al Choiri; Mochamad Nurhadi (STIE Perbanas Surabaya, 2018)
The aim of this research are to find more information and empirical evidence about the influence of corporate social responsibility and brand images to purchase intention and the influence of brand images in mediating the relationship between corporate social responsibility (CSR) to purchase intention. This research uses 110 Surabaya people who are at least 20 years old who have never used Telkom products and and intend to buy Telkom products, have knowledge about corporate social responsibility programs implemented by Telkom. This is a quantitative research, which data will be analyzed by using Partial Least Squares Structural Equation Modelling (PLS-SEM). The result of this research shows that corporate social responsibility (CSR) have no significant effect on purchase intention, corporate social responsibility (CSR) have significant effect on brand images, brand images have significant effect on purchase intention brand images can’t mediate the relationship between corporate social responsibility (CSR) on purchase intention.